Application of Lean Techniques to Reduce Preparation Times: Case Study of a Peruvian Plastic Company - Silva Reyes, Alfredo Jeampiere (2017)
This article examines the problem of an increase in product returns for a company that produces plastic films for flexible packaging. Among the factors that have resulted in the increase of returned products are defects in the films caused by the poor manipulation of materials and, above all, the hard point in the coils caused by excessive extruder preparation time, causing the extrusion head to overheat as well as uneven extrusion. Extrusion is a key process in the production of plastic materials as it transforms polypropylene and additives into plastic sheets. The delay in the preparation time caused by machine operators leads to the overheating of the extrusion head and, therefore, defective products that are ultimately returned to the company by customers. In order to confront this problem, a proposal was developed using the SMED tool of Lean Manufacturing in order to reduce the preparation time of the extruder and to increase the productivity of the company. For the validation of the proposal, we simulated the system to determine the resulting reduction in extruder preparation time.